Assessment of Utility of Carbamylated Hemoglobin in Determining the Overall Adequacy of Hemodialysis (Academia Journal of Medicine, 2021)
Background: CKD is characterized by progressive and ongoing loss of kidney function of not 0.05). The regression equation at 3 months is CHb. = 482.33 + 0.122 age (Yrs) – 0.492 gender + 0.192 duration(months) - 0.624 HD frequency/wks(Hrs) - 0.207 HD vintage(months) + 0.063 BMI + 6.021 Hb.(gm%) + 0.011 BUL(mg/dl) – 0.191 Creatinine(mg/dl) + 0.123 Na(mmol/l) – 1.047 K(mmol/l) + 5.642 Alb.(gm/dl) – 55.12 pH + 0.903 HCO3 - 0.018 iPTH(pg/ml) – 11.54 Kt/V – 96.54 Valine hydantoin absorbance + 0.005 Blood Flow Rate (ml/min). Conclusion: Carbamylated haemoglobin had a direct correlation with blood urea nitrogen levels and with serum creatinine levels in chronic kidney disease patients on maintenance haemodialysis.
Keywords: Carbamylated haemoglobin; Serum creatinine; Haemodialysis